Innovation of Adaptive Learning Based on Artificial Intelligence - Rompas, Parabelem Tinno Dolf; Lalompoh, Hartentus M.; Wagei, Suci K.; Gunde, Alfrits P.; Batmetan, Johan Reimon (JR Education, 2025)
The development of digital technology encourages transformation across various sectors, including education. Adaptive learning based on Artificial Intelligence (AI) is an innovation that enables the teaching and learning process to take place in a personalized, dynamic manner, and aligned with students’ characteristics. This article discusses the implementation of AI-based adaptive learning as a strategy to improve learning effectiveness through learning needs analysis, curriculum differentiation, and the use of data as the basis for learning recommendations. The research method employed is a literature study by reviewing recent journals and scientific publications. The findings show that AI-based adaptive learning can increase learning motivation, independence, and learning achievement through the delivery of materials aligned with students’ competency levels, learning styles, and learning pace. In conclusion, this innovation becomes a potential solution for improving the quality of education in the digital era, provided that technological infrastructure, teacher readiness, and students’ digital literacy are adequately supported.